Butterfly and moth diversity of Krong Trai nature reserve, Phu Yen province - Thanh Binh, Tran Thi; Lien, Vu Van (Academia Journal of Biology, 2014)
A study of Lepidopteran diversity was carried out from 5 to 25 September 2012, at 6 transects of different habitats at Krong Trai Nature Reserve, Son Hoa District of Phu Yen Province. The transects that are representative for almost all habitats of the Reserve: secondary forest near the natural forest, poor evergreen secondary forest, semi-dry forest, shrub and grass habitat, and agro-forestry land (rice, corn, manioc). Among the habitats, the semi-dry habitat is the poorest habitat; the secondary forest is the most diversity habitat. The result identified 140 species of butterflies (122 species) and moths (18 macro moth species). The majority species are rare (1-2 individuals) with 63 species (45% of all species). The secondady forest has highest species and individual numbers, and highest diversity index; the semi-dry forest has the lowest species and individual numbers, and lowest diversity index. One butterfly species is listed in the Red Data Book of Vietnam and CITES is Troides aeacus. One new record species for Vietnam animal fauna is Cowania achaja.